2019
DOI: 10.22207/jpam.13.3.19
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical and Antimicrobial Activity Evaluation of The Water Immiscible Solvent Extracts of Moringa

Abstract: Antimicrobial resistance (AMR) is the existing global apprehension for the social health. There is a requisite to take counteractive actions regarding the AMR. Based on the literature, it was aimed to perform the phytochemical and antimicrobial activity evaluation of the water immiscible solvent extracts of Moringa peregrina Forssk. Fiori (Family: Moringaceae). Seven extracts of the powdered leaves of M. peregrina were prepared in solvent systems comprising dichloromethane (DCM), dichloroethane (DCE), and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…The ethanol and aqueous seeds extract of Ziziphus jujube revealed the presence of secondary metabolites, which are alkaloids, saponins, flavonoids, phenols, glycosides, anthocyanin, betacyanin, and steroids (Abd-Alrahman et al, 2013). On another note, Washid and Ameeta (2011) reported that Z. xyloperus ethanol leaf extract contained glycosides, phenols/tannins, high concentrations of flavonoids, saponins, carbohydrates, and steroids using column chromatographic screening.…”
Section: Literature Review Secondary Metabolites Of Ziziphus Speciesmentioning
confidence: 99%
“…The ethanol and aqueous seeds extract of Ziziphus jujube revealed the presence of secondary metabolites, which are alkaloids, saponins, flavonoids, phenols, glycosides, anthocyanin, betacyanin, and steroids (Abd-Alrahman et al, 2013). On another note, Washid and Ameeta (2011) reported that Z. xyloperus ethanol leaf extract contained glycosides, phenols/tannins, high concentrations of flavonoids, saponins, carbohydrates, and steroids using column chromatographic screening.…”
Section: Literature Review Secondary Metabolites Of Ziziphus Speciesmentioning
confidence: 99%